Formulation, optimization, and photostability assessment of microemulsion gel for topical quercetin delivery - Khonkarn R. (2017)
© 2017, Colegio de Farmaceuticos de la Provincia de Buenos Aires. All rights reserved. The present study aims to optimize formulations and evaluate the stability of quercetin which was loaded into microemulsion and microemulsion-based gel to treat keloids. The results show that the optimal microemulsion formulation to incorporate quercetin consisted of Tween 80, Transcutol, Capryol 90, and water. Further, the quercetin-incorporated microemulsion-based gel (QMG) was successfully formulated using 15% Carbopol Aqua as the gelling agent. To analyze the photostability, controlling the pH of the microemulsion to 7.4 could improve the photostability of the loaded quercetin. Although the permeability of QM was significantly higher than that of QMG, the superior quercetin, which was retained in porcine skin, was found from QMG at 6 h after the application. It was concluded that microemulsion based gel can be considered as an attractive formulation for skin delivery of quercetin to treat keloids.